Rendering Strategy to Counter Mutual Masking Effect in Multiple Tactile Feedback - Semin Ryu (Applied Sciences, 2020)
Recently, methods and devices that simultaneously utilize two or more tactile feedback types have been proposed for more immersive interaction with virtual objects. However, the masking effect, which makes us less sensitive to various stimuli presented at the same time, has scarcely been explored. In this study, we propose a novel tactile rendering algorithm that can eliminate the mutual masking effect at the user’s sensation level, when mechanical vibration and electrovibration are applied simultaneously. First, the masking functions of the two stimuli were investigated for various stimulus combinations. Based on these, a generalized form of the masking function was derived. We then tested and confirmed that the proposed algorithm, which calculates the required stimulus intensity to compensate for the mutual masking effect, could render the arbitrary stimulus intensity desired to be perceived by the users. The results of the user test revealed that the proposed rendering algorithm significantly improved the virtual object recognition rate by approximately 23% when geometry and texture were presented jointly. This finding suggests principal guidelines for the combined use of mechanical vibration and electrovibration, as well as for other combinations of different tactile feedback types.